2015
DOI: 10.1534/genetics.115.182311
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Short-Read Sequencing and Aneuploidy Detection Using MinION Nanopore Technology

Abstract: MinION is a memory stick–sized nanopore-based sequencer designed primarily for single-molecule sequencing of long DNA fragments (>6 kb). We developed a library preparation and data-analysis method to enable rapid real-time sequencing of short DNA fragments (<1 kb) that resulted in the sequencing of 500 reads in 3 min and 40,000–80,000 reads in 2–4 hr at a rate of 30 nt/sec. We then demonstrated the clinical applicability of this approach by performing successful aneuploidy detection in prenatal and miscarriage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
0
48
1
Order By: Relevance
“…The typical turnaround time for aneuploidy detection in such samples is 1–3 weeks when using NGS platforms [59]. Wei and Williams [38] used the MinION to detect aneuploidy in prenatal and miscarriage samples in under 4 h. They concluded that the MinION can be used for aneuploidy detection in a clinical setting.…”
Section: Current Applications Of the Minionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical turnaround time for aneuploidy detection in such samples is 1–3 weeks when using NGS platforms [59]. Wei and Williams [38] used the MinION to detect aneuploidy in prenatal and miscarriage samples in under 4 h. They concluded that the MinION can be used for aneuploidy detection in a clinical setting.…”
Section: Current Applications Of the Minionmentioning
confidence: 99%
“…To date, only MinION-based strand sequencing has been successfully employed by independent genomics laboratories. Where possible, this review focuses on peer-reviewed research performed using the MinION [1, 738]. …”
Section: Introductionmentioning
confidence: 99%
“…Future diagnostic support could revolutionize the ability of the researchers working in the public health sector to perform sequencing during future disease outbreaks. Other diagnostic applications have also been reported, including prediction of antibiotic resistance by sequencing the genomes of Staphylococcus aureus and Mycobacterium tuberculosis [62]; real-time strain typing and analysis of antibiotic resistance [63]; and aneuploidy detection in prenatal and miscarriage samples with sequencing reads generated in less than 4 h [64] just to name a few. Please visit https://publications.nanoporetech.com for an up-to-date list of applications and publications using ONT sequencing.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Both of these technologies are more error-prone than current NGS systems, but workarounds are possible with a hybrid sequencing effort, using high-quality NGS short read information for error correction in the longer TGS reads [141]. Furthermore, despite these error rates, it has been demonstrated that even at extremely low coverage (58,000 reads compared to Illumina or Ion’s millions of reads typically generated), MinION has potential clinical applications in prenatal testing, accurately assessing aneuploidy in 2–4 hours using a short read sequencing library preparation [142]. …”
Section: Sequencing: the Next And The Next-next Generationmentioning
confidence: 99%